Voriconazole: The Latest Triazole Antifungal Compound - Sugandhi, Om Guptesh; Patil, Dhananjay; Gangurde, Gokuli; Nutan, Bagul; Kashid, Vivekanand; Pathan, Musab; Chaudhari, Swati (Journal of Neonatal Surgery, 2025)
Voriconazole, a novel second-generation triazole antifungal, has significantly expanded the therapeutic landscape for invasive fungal infections. Its broad-spectrum activity against Aspergillus spp., Candida spp., Scedosporium apiospermum, and Fusarium spp. makes it a vital agent, particularly in immunocompromised populations. With excellent oral bioavailability (>95%) and the availability of both intravenous and oral formulations, voriconazole offers clinical flexibility and cost-effectiveness, especially when transitioning from hospital to outpatient care. Clinical trials have shown its superior efficacy over amphotericin B in treating invasive aspergillosis and comparable outcomes to fluconazole in esophageal candidiasis. Despite its clinical advantages, voriconazole’s use must be carefully managed due to potential adverse effects such as visual disturbances, hepatotoxicity, and drug–drug interactions via cytochrome P450 enzymes. Genetic polymorphisms, particularly in CYP2C19, can result in significant interindividual variability in metabolism and drug exposure. Resistance, although still limited, has been observed, particularly in azole-resistant fungal strains, raising concerns for future clinical efficacy. Pharmacoeconomic evaluations support voriconazole's cost benefit when oral therapy is introduced early in treatment. In summary, voriconazole represents a powerful tool in antifungal therapy, provided it is used with individualized dosing and vigilant monitoring to mitigate toxicity and resistance risks.